Hydraulic design of labyrinth weirs - Falvey, Henry T. (Reston, Virginia ASCE Press, 2003)
"Hydraulic Design of Labyrinth Weirs is a comprehensive treatise on the hydraulic design of labyrinth spillways. The book begins with a section on the theory of labyrinth weirs and continues with detailed sections on significant factors that affect the discharge characteristics such as crest shape, weir height, and sidewall angle. The design of a labyrinth weir and modeling criteria is also covered. Several prototype labyrinth spillway configurations are included as examples."
Includes bibliographical references (p. 149-160) and index.
Keywords: Labyrinth weirs -- Design and construction; Electronic books